Ananas comosus L. bio-waste as a potential source of phenolic compounds with food application - Moreira, Bruna (2022)
Pineapple (Ananas comosus [L.] Merr.) is one of the much-appreciated fruit and consumed worldwide not only for its nutritional properties, but also for being recognized for its beneficial characteristics with action on consumer health. However, a large percentage of this fruit is represented by the crown leaves and peel that are not consumed and, industrially, are not exploited. In addition, the fruit pulp processing industries generate tons of various waste, which has aroused great economic and environmental concern, since disposal solutions are quite limited. In this sense, the present study aimed to characterize the phenolic profile of the peel and the crown leaves as well as to evaluate its bioactive potential, aiming in the application of the most promising extract in a pastry product as a natural ingredient with potential application in the food industry. The phenolic compounds of both matrices were extracted using a heat-assisted hydroethanolic extraction, and subsequently identified and quantified by high performance liquid chromatography coupled with diode detector and mass spectrometry detector (HPLC-DAD-ESI/MS). Twenty-five phenolic compounds were identified in both extracts, comprising phenolic acids and flavonoids. The main compounds detected were caffeic acid derivatives and glycoside flavones, such as apigenin 6,8-C-diglucoside. The antioxidant activity of the extracts was tested by two in vitro tests: the lipid peroxidation inhibition assay (TBARS) and the oxidative hemolysis inhibition assay (OxHLIA). The antiproliferative activity of both extracts was evaluated in tumor (MCF-7, NCI-H460, AGS and CaCo-2) and non-tumor (VERO) cell lines using the sulforhodamine B method. Finally, the antimicrobial activity was evaluated, testing the potential of both extracts against a panel of six bacteria and six fungi. The results revealed that both extracts showed an excellent performance in terms of bioactive assays and demonstrated that none of the extracts showed toxicity up to the maximum concentration tested (GI50 > 400 μg/mL), proving its application potential as a natural ingredient. Despite the excellent results, the peel extract stood out, presenting an antioxidant and antimicrobial potential superior to that presented by the crown leaves extract, having therefore been selected for being incorporated in a typical Portuguese pastry product, called “súplicas". The effects of incorporating the natural ingredient on the chemical and proximate composition of the "súplicas" were evaluated over different shelf life (0, 3 and 7 days after incorporation) and compared with the traditionally produced product. The proximate composition (ash, fats, proteins, carbohydrates contents and energy value) was determined through official methodologies of food analysis (AOAC), while the individual chemical composition was obtained by quantifying the fatty acid content through Gas Chromatography coupled to a Flame Ionization Detector (GC-FID) and the sugar content by HPLC coupled to a refraction index. Also, the variation in colour parameters (L*, a* and b*) was evaluated in all samples of all times. The results showed that the extract did not cause changes in proximate composition, sugar and fatty acid content and in colour parameters. In turn, the evaluation of the antioxidant activity of the “súplicas” revealed that the incorporation of the extract increased the antioxidant potential of the food product compared to the traditional recipe. Thus, this study confirms the potential application of this pineapple bio-waste as a source of bioactive compounds, aiming at reusing a low-cost natural resource and directly contributing in the environmental and economic impact.